VOICES OF DISABLED STUDENTS IN INCLUSIVE EFL CLASSROOMS: A SYSTEMATIC REVIEW - Effendi, Taufiq (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This review investigates the state of research in English as a foreign Language teaching scholarship regarding the voices of disabled students in EFL inclusive classrooms. Out of 761 studies generated from British Education Index, Education Abstracts, Education Source, Scopus and Web of Science, only two studies met the eligibility criteria for inclusion. Hand-searching of the references from the two studies resulted in four relevant studies for inclusion. These studies were carried out in South America (n=2), Indonesia (n=2), Greece (n=1) and Turkey (n=1). This limited number of studies suggests that voices of disabled students in EFL scholarship have not been given enough importance regardless the global celebration of inclusive education agenda. The findings of this review highlight recommendations for future research, policy and practices in the field of EFL education.